Performing childhood: Maddie Ziegler and the presentation of young girls in video clips - Mehrbrey, Sophia (Jeunesse, 2023)
Since the 1980s, the production of video clips has been on the rise. Over the past couple of years, clips showing dance choreographies, often embedded within a rather conceptual fictional framework, have greatly increased in popularity. Although the musicians are usually adults, it is not uncommon to cast children and young adults to perform in the videos. At the same time, multiple reality TV formats in which children and young adults compete performing dance choreographies to famous pop songs have become a popular form of entertainment. The American TV series Dance Moms is a prominent example of this phenomenon. One of the best-known young artists in the field is Maddie Ziegler, who made her debut in this show and subsequently appeared in several music videos by the singer Sia. Maddie, born in 2002, was eleven years old when she first performed in a video clip. Her career is emblematic of the presentation of young girls in a popular culture and media that is dominated by the deliberate play with expectations of age and the blurring of categorical distinctions. Drawing on Maddie Ziegler as an example, the following article provides a close analysis of the presentation of young girls in video clips and reality shows. Special attention is given to the atemporal image of adolescence in these adult reconstructions, which, instead of celebrating the rebellious potential of youth, oscillate between the angelic outer appearance of the child and the serious demeanour of the adult.
Online veröffentlicht: 18. Mai 2023
Gesehen am 22.01.2025